Analysis of Recent Growth in Low-Income CIS Countries - Loukoianova, Elena (IMF Working Papers; Working Paper ;, 2004)
This paper analyzes factors that determine recent economic growth in the low-income countries of the Commonwealth of Independent States.2 The main findings are as follows: (1) productivity gains in export-oriented sectors and expansion of exports may have become the main sources of growth in five of the seven CIS-7 countries, while in the early years of transition the output recovery was mainly driven by consumption; (2) economic growth has concentrated in agriculture and the raw material sectors, and, thus, is vulnerable to changes in external conditions; and (3) structural reforms matter for growth, which is consistent with previous research on growth in transition countries.